Propagation and attenuation of guided waves in stressed viscoelastic waveguides. (December 2019) - Li, Chunlei; Han, Qiang; Wang, Zhan; Liu, Yijie
The motion of guided waves in viscoelastic waveguides is generally accompanied by energy transport and dissipation. Envisioned applications demand an accurate understanding of both propagating and evanescent of waves related to dispersive properties. This paper uses the isogeometric analysis to consider wave characteristics in stressed viscoelastic waveguides based on the Floquet's principle. Parameterized wave equation considering the acoustoelasticity and viscoelasticity is obtained from the virtual power principle and the updated Lagrangian format. In addition, the energy velocity of a guided wave mode is derived in the linear incremental theory. Error estimations of cutoff frequencies for flexural wave modes are shown for the comparison between the wave isogeometric analysis method and the classic wave finite element method. The results indicate the former can provide smaller error compared with the latter. Then, phase velocity, energy velocity, and wave attenuation are presented for two kinds of viscoelastic structures (double cylindrical rods, functionally graded material plates) under different loaded cases. The effects of stress and viscoelasticity are also demonstrated in detail.